The European Large Area ISO survey - VIII. 90-mu m final analysis and source counts - Heraudeau, P; Oliver, S; del Burgo, C; Kiss, C; Stickel, M; Mueller, T; Rowan-Robinson, M; Efstathiou, A; Surace, C; Toth, L; Serjeant, S; Alexander, D; et al. (2004)
We present a re-analysis of the European Large Area Infrared Space Observatory (ISO) Survey (ELAIS) 90-μm observations carried out with ISOPHOT, an instrument on board the ISO of the European Space Agency. With more than 12 deg2, the ELAIS survey is the largest area covered by ISO in a single programme and is about one order of magnitude deeper than the IRAS 100-μm survey. The data analysis is presented and was mainly performed with the PHOT interactive analysis software but using the pairwise method of Stickel et al. for signal processing from edited raw data to signal per chopper plateau. The ELAIS 90-μm catalogue contains 237 reliable sources with fluxes larger than 70 mJy and is available in the electronic version of this article. Number counts are presented and show an excess above the no-evolution model prediction. This confirms the strong evolution detected at shorter (15 μm) and longer (170 μm) wavelengths in other ISO surveys. The ELAIS counts are in agreement with previous works at 90 μm and in particular with the deeper counts extracted from the Lockman hole observations. Comparison with recent evolutionary models show that the models of Franceschini et al. and Guiderdoni et al. (which includes a heavily extinguished population of galaxies) give the best fit to the data. Deeper observations are nevertheless required to discriminate better between the model predictions in the far-infrared, and are scheduled with the Spitzer Space Telescope, which has already started operating, and will also be performed by ASTRO-F.